Les séries de Dirichlet avec une distribution irrégulière des arguments des exposants - Lunts, G. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Г. Л. Лунц. Ряды Дирихле нерегулярным распределением аргументов показателейG. Luncas. Dirichle eilutės, kurių rodiklių argumentų sekos nėra reguliariai pasiskirsčiusios